Associação entre variáveis bucais, obesidade e hipertensão em uma população rural do sul do Brasil: um estudo transversal - Carlotto, Israel Bangel (2024)
This thesis is composed of two studies. The objective of the first study was to test the hypothesis that dental caries, periodontal burden, endodontic burden, oral inflammatory burden, and tooth loss are independently associated with hypertension in a rural population in southern Brazil. In this secondary analysis, derived from a cross-sectional study, the outcome was systemic arterial hypertension. Its association with oral health exposure variables was analyzed using univariate and multivariate Poisson regressions with robust variance to estimate Prevalence Ratios (PR) and 95% Confidence Intervals, in models adjusted for sociodemographic and medical variables, with α=5%. Among the 562 participants, 240 (42.7%) had systemic arterial hypertension. The univariate analysis showed that age ≥60 years, education ≤8 years, BMI ≥25 and <30, BMI >30, waist circumference with a substantially increased risk, diabetes, DMFT >12, severe periodontal burden, apical periodontitis >2, endodontic burden ≥3, moderate oral inflammatory burden, severe oral inflammatory burden, and tooth count <20 were associated with hypertension. Multivariate models, adjusted for sociodemographic and medical variables, showed that DMFT >12 (p=0.000), severe periodontal burden (p=0.004), endodontic burden ≥3 (p=0.040), severe oral inflammatory burden (p=0.003), and tooth count <20 (p=0.016) were independently associated with hypertension. The hypothesis that oral health variables were independently associated with hypertension in this rural population was confirmed. This study may serve as a foundation for future longitudinal research to explore these associations more deeply. The objective of the second study was to test the hypothesis that dental caries, oral inflammatory burden, and tooth loss are independently associated with obesity in a rural population in southern Brazil. In this secondary analysis, univariate and multivariate Poisson regressions with robust variance were used to estimate Prevalence Ratios (PR) and 95% Confidence Intervals for the associations between DMFT, oral inflammatory burden, tooth loss, and waist circumference. Models were adjusted for sociodemographic and medical variables, with a significance level set at α=5%. Among the 562 participants, 242 (43%) had a waist circumference with a substantially increased risk of metabolic complications. The univariate analysis showed that age ≥60 years, male gender, non-white ethnicity, current smokers, AUDIT ≥8, hypertension, diabetes, and tooth count <20 were associated with waist circumference. Multivariate models, adjusted for sociodemographic and medical variables, showed that tooth count <20 (p=0.045) was independently associated with waist circumference. In this rural population, tooth loss was shown to be independently associated with obesity. Longitudinal studies are needed to explore this association over time.